Exploring the influence of Facebook reels on consumer brand attitude and purchase intentions - Babu Md Asaduzzaman; Shekh Md Jaman Sahiduj; Rini Gulshan Ara; Hossain Md Arman (Marketing (Beograd. 1991))
The study aims to investigate reel videos' potential influence on consumer purchasing intentions on Facebook. The study employed a non-probability sampling method and gathered data from 203 respondents through an online survey in Dinajpur, Bangladesh. Smart PLS 4.1.0.0 was used to analyze the data using the partial least squares-structural equation modeling (PLS-SEM) approach. According to the study's findings, brand attitudes significantly influence purchase intention. These interactions significantly influence the company's marketing decisions and the buying intentions of its customers. This research is fueled by the significant number of internet users in Bangladesh and their reliance on Facebook, which provides valuable services, including the reel function. The study provided suggestions on how companies can enhance the quality and content of platforms for short videos, thereby boosting the effectiveness of their marketing campaigns. It would be beneficial to conduct a more in-depth analysis of the organization's promotional policies and their impact on market share.